2017
DOI: 10.1097/qai.0000000000001440
|View full text |Cite
|
Sign up to set email alerts
|

Optimal HIV Postexposure Prophylaxis Regimen Completion With Single Tablet Daily Elvitegravir/Cobicistat/Tenofovir Disoproxil Fumarate/Emtricitabine Compared With More Frequent Dosing Regimens

Abstract: Structure The study evaluated elvitegravir/cobicistat/tenofovir disiproxil fumarate(TDF)/emtricitabine(FTC) (“Quad pill”) for post-exposure prophylaxis (PEP). Background HIV-exposed individuals may benefit from PEP, but completion rates have been suboptimal because of regimen complexity and side effects. Newer antiretroviral combinations co-formulated as single daily pills may optimize PEP adherence. Setting One hundred HIV-uninfected individuals who presented to a Boston community health center after an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
15
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 39 publications
(39 reference statements)
1
15
0
1
Order By: Relevance
“…In 2021, almost a decade prior to the start of COVID-19, the US Food and Drug Administration approved the use of PrEP for HIV prevention (U.S. Food and Drug Administration, 2012 ), adding another biomedical tool to combat the HIV epidemic beyond treatment as prevention and PEP. Whereas non-occupational PEP is a three- or four-drug regime of antiretrovirals administered within 72 h after a potential HIV exposure recommended by the CDC since 2005 (CDC, 2017c ; Smith et al, 2005 ) to reduce the risk of HIV seroconversion (Mayer et al, 2017 ), PrEP in its current form is a once-daily pill regime supported by CDC prescribing guidelines to be taken before HIV exposure events (CDC, 2017c ). While fewer than 12% of HIV-negative or unknown status SMM have reported taking PEP in their lifetime (John et al, 2021 ), there was a 470% increase in PrEP uptake in individuals over 16 years old, predominantly among cisgender men, between 2014 and 2016 (Ya-lin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, almost a decade prior to the start of COVID-19, the US Food and Drug Administration approved the use of PrEP for HIV prevention (U.S. Food and Drug Administration, 2012 ), adding another biomedical tool to combat the HIV epidemic beyond treatment as prevention and PEP. Whereas non-occupational PEP is a three- or four-drug regime of antiretrovirals administered within 72 h after a potential HIV exposure recommended by the CDC since 2005 (CDC, 2017c ; Smith et al, 2005 ) to reduce the risk of HIV seroconversion (Mayer et al, 2017 ), PrEP in its current form is a once-daily pill regime supported by CDC prescribing guidelines to be taken before HIV exposure events (CDC, 2017c ). While fewer than 12% of HIV-negative or unknown status SMM have reported taking PEP in their lifetime (John et al, 2021 ), there was a 470% increase in PrEP uptake in individuals over 16 years old, predominantly among cisgender men, between 2014 and 2016 (Ya-lin et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…The Boston community health center where the trial was conducted has maintained the largest PEP program in New England for more than 20 years, 19 and has been actively investigating new, potent, and better tolerated regimens for PEP since then. 11,12,20…”
Section: Introductionmentioning
confidence: 99%
“…There is a demand for PEP regimens that could overcome challenges of poor adherence, severe adverse events, and dosing convenience. Two previous overseas studies using co-formulated STRs (elvitegravir/cobicistat/tenofovir disoproxil fumarate/emtricitabine) of HIV PEP found that the majority of participants achieved a higher drug completion rate (> 70%) and favorable drug tolerance [ 11 , 12 ]. However, these studies did not include Chinese participants or cohorts, and the real-world usage of these STRs in China was low.…”
Section: Introductionmentioning
confidence: 99%